(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2016)
Introduction: Necrotizing enterocolitis (NEC) is a major cause of neonatal morbidity and mortality. To explore whether abdominal ultrasound (AUS) provide additional information over plain radiography in cases of necrotizing enterocolitis (NEC). Materials & Methods: This study is a prospective study of 30 premature neonates with NEC in our neonatal intensive care unit between September 2013 and November 2014. Fifteen premature control neonates were also included in the study. Results: Patients were classified into two groups: the first group with suspected NEC (stage I) (n = 14) and the second with definite NEC (stage II or III) (n = 16). In group I abdominal ultrasound (AUS) revealed intramural air (n = 9) and portal venous gas (PVG) (n = 1) while plain radiography showed only gaseous distension. In group II, intramural air (n = 10), PVG (n = 2), free fluid (n = 6) focal fluid (n = 1) and free air (n = 6) detected by AUS compared to pneumatosis intestinalis (PI) (n = 2) PVG (n = 1) and free air (n = 5) by plain radiography. Additionally bowel wall thinning was detected in 2 neonates of group I and 3 of group II. Conclusion: Our results suggest AUS to be superior to plain radiography in early detection of complication as intestinal perforation by eliciting PVG and fluid collection and so early surgical management. Therefore this may decrease morbidity and mortality rates. J. Paediatr. Surg. Bangladesh 6(2): 47-53, 2015 (July)